2022
DOI: 10.1530/etj-21-0001
|View full text |Cite
|
Sign up to set email alerts
|

Does foetal gender influence maternal thyroid parameters in pregnancy?

Abstract: Objective It is unknown if foetal gender influences maternal thyroid function during pregnancy. We therefore investigated the prevalence of thyroid disorders and determined first-trimester TSH reference ranges according to gender. Methods A cross-sectional study involving 1663 women with an ongoing pregnancy was conducted. Twin and assisted pregnancies and l-thyroxine or antithyroid treatment before pregnancy were exclusion criteria. Serum TSH, free T4 (FT4) and thyroid peroxidase antibodies (TPOAb) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In one study in euthyroid women, TPOAb positivity was strongly associated with PTB, but only in case of pregnancies with female foetuses [33]. Furthermore, in a recent study by Sitoris et al, it was observed that serum TSH levels in women pregnant with a female foetus were higher compared with those in women pregnant with a male one, probably due to differences in hCG levels and/or other placental factors [34].…”
Section: Discussionmentioning
confidence: 92%
“…In one study in euthyroid women, TPOAb positivity was strongly associated with PTB, but only in case of pregnancies with female foetuses [33]. Furthermore, in a recent study by Sitoris et al, it was observed that serum TSH levels in women pregnant with a female foetus were higher compared with those in women pregnant with a male one, probably due to differences in hCG levels and/or other placental factors [34].…”
Section: Discussionmentioning
confidence: 92%
“…Another parameter for which in more recent studies an adjustment is made is the fetal gender. Previous studies have shown that maternal TSH levels were lower in women pregnant with a female fetus, probably due to higher hCG levels and/or other placental substances like the vascular endothelial growth factor with an impact on thyroid vascularisation ( 24 ). Moreover, in one study, thyroid disorders were associated with PTB only in case of pregnancies with a female fetus ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have also shown that the fetal gender might lead to changes in thyroid function ( 23 ). In our study, no differences were observed in TSH values between pregnant women who gave birth to MF and those who gave birth to FF in each trimester.…”
Section: Discussionmentioning
confidence: 99%